Readiness of Legazpi City, Albay in Becoming the Top 5 Meetings, Incentives, Conventions and Exhibitions (MICE) Destination in the Philippines - Gonzales, Maria Luisa (JPAIR Multidisciplinary Research, 2019)
Tourism played a significant role in the development of a country’s economic development. Tourist expenditures contributed a lot to the economy of destination areas. This tourism activity illuminated MICE to be a unique opportunity for the development of a certain locality. This study determined the readiness of Legazpi City in becoming one of the top 5 MICE destinations in the Philippines, aimed to determine the perceptions of the respondents towards hotel/resorts, convention/exhibition centers, and public/private sectors along with its physical, technology, and services offered, likewise, the challenges encountered by the industry. It uses the descriptive method of research employing a survey instrument lifted from ASEAN MICE Venue Standard to 160 respondents of the study was 100 are tourists, ten from Local Government Unit, and 50 Private sectors. Findings revealed that the city is on the result of the study. However, challenges were identified, such as City Planning, External Competition, complete vulnerability, information technology revolution, and human resources are the city’s difficulties. Thus, this research will provide conceptions of a logical framework that will resolve the city’s dream of inclusion to be one of the top 5 MICE destinations.